Less Masculine, More Feminine dan Less Feminine, More Masculine: Laki-laki Mengekspresikan Androgini Melalui Fashion - Putri Kumalasari Fadly WIjayakusuma (Universitas Muslim Maros, 2020)
Androgyny combines masculine and feminine characters at once. Despite the fact that the way one’s talk, gestures, emotions, interests and talents are indicators of androgyny, fashion or the way they dress has become the main indicator. While the existing literatures deal more on characteristics, behavior, interests and talents, and self-representation through social media, this article is focused on how androgyny men exptress their gender through fashion. This study was conducted in the city of Makassar which involved 12 male college students. They are varied based on age (between 20 and 24 years), and profession (master of ceremony, model, dancer, make up artist, disc jockey). Data was collected using in-depth interview, focus discussion group (FGD), and observation as the primary data sources as well website and social media (i.e. Instagram), as the secondary data sources. The study indicates that androgynous men is not transgender because they did not want to become “like women”, as transgender do. Besides, androgynous men classify themselves higher than transgender, from both appearance and social class. Although androgynous men may express their androgynousness through behavior, interests and talents, fashion is the most significant aspect that indicates a person's androgynousity. Androgynous men express androgyny more through fashion than others because through fashion their existence is easily recognized, as it is combining between masculine and feminine characters. Androgynous fashion is divided into two, less masculine-more feminine and less feminine-more masculine. Whether an androgynous man is more feminine or more masculine, depending on their performance and perception towards what is being performed. The motives of androgynous men are divided into two, the first is “because-to-motive” and “in-order to motive”. While the former includes influencing by peer group, having sense of comfort, feeling self satisfaction, and being professional; the latter consists of expecting to be socially accepted and to be accepted as normal people.